TREATMENT OF INTERNAL CAROTID ARTERY OCCLUSION USING PROXIMAL CEREBRAL PROTECTION DEVICE AND ITS EFFECT ON THE BLOOD PRESSURE DYNAMICS. CLINICAL CASE - F. В. Shukurov; D. S. Chigidinova; E. S. Bulgakova; B. A. Rudenko; T. V. Tvorogova; A. S. Shanoyan; O. M. Drapkina (Столичная издательская компания, 2018)
In 2016, according to the Ministry of Health of the Russian Federation, about 200 thousand people died from stroke. Strokes are considered as the main cause of disability of the population, causing huge economic damage to the country. One of the most common causes of ischemic stroke is atherosclerosis of the branches of the aortic arch. The most common localization of atherosclerotic plaques is the extracranial section of the carotid arteries - bifurcation and ostium of the common carotid artery and the internal carotid artery. Recanalization of occlusion of the internal carotid artery until recently was an insoluble task for interventional surgery due to the high risk of distal embolization. The invention and use of the proximal cerebral protection device, which ensure the complete cessation of blood flow, has changed the situation. Effect of carotid revascularization on arterial hypertension, due to the effect on the baroreceptors of the carotid plexus by balloon angioplasty, which leads to a reflex decrease in arterial pressure, is an additional advantage of the endovascular technique in some cases. This effect requires further study. One also needs to pay careful attention to the diagnosis and imaging of carotid artery lesions before procedure. This clinical case is the illustration that an adequate assessment of the risk factors for intraoperative complications allows to achieve maximum results of endovascular treatment.